Minat Siswa Sekolah Menengah Kejuruan Memilih Program Studi Meeting, Incentive, Conference, Exhibition di Politeknik Negeri Medan - Sarah Rouli Tambunan (Universitas Negeri Medan, 2020)
This paper wants to explain whether vocational students in the field of tourism in Medan are aware of the MICE industry (Meeting, Incentive, Conference, Exhibition) and MICE study programs in Politeknik Negeri Medan (Polmed). Furthermore, how is the interest of tourism vocational school students in Medan before and after being given a stimulus. The research uses descriptive method with quantitative approach. Data collection was carried out through a survey technique using a questionnaire. The respondent is tourism vocational school student in class which is spread in 15 vocational schools in Medan. The results showed that from 150 respondents surveyed, only 52% knew about the MICE industry, even though MICE was related to tourism. Furthermore, only 32% of respondents are aware of the existence of the MICE study program in Polmed. The low knowledge of students about MICE Polmed study program, effect the low interest of respondents in choosing this study program that is only by 8%. However, increased interest was seen when respondents had received stimulus in the form of information about the MICE Polmed study program profile which was displayed using media: books and videos. From 8% of respondents who were initially interested in choosing the MICE Polmed study program, after being given a stimulus it increased to 73.66%.